2013
DOI: 10.1088/1748-9326/8/3/035007
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting response of grassland versus forest carbon and water fluxes to spring drought in Switzerland

Abstract: Since the European summer heat wave of 2003, considerable attention has been paid to the impacts of exceptional weather events on terrestrial ecosystems. While our understanding of the effects of summer drought on ecosystem carbon and water vapour fluxes has recently advanced, the effects of spring drought remain unclear. In Switzerland, spring 2011 (March-May) was the warmest and among the driest since the beginning of meteorological measurements. This study synthesizes Swiss FluxNet data from three grassland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
127
4
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 41 publications
11
127
4
1
Order By: Relevance
“…Such a strong effect of droughts (compared to high temperatures alone) on GPP and the generally decreasing effect of drought on GPP is consistent with other studies (e.g. Ciais et al, 2005;Zhao and Running, 2010;Wolf et al, 2013;Zscheischler et al, 2014a, d, c) where water stress directly forces plants to close their stomata to limit transpiration, reducing photosynthesis. Similarly, Jung et al (2017) found that water availability is a much bigger control on the inter annual variability of GPP (IAV, which is controlled to a large degree by extreme events) compared to a smaller temperature control on a global In contrast to the small response of GPP to heat, however, R eco generally increased during most high temperature extreme events (Fig.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Such a strong effect of droughts (compared to high temperatures alone) on GPP and the generally decreasing effect of drought on GPP is consistent with other studies (e.g. Ciais et al, 2005;Zhao and Running, 2010;Wolf et al, 2013;Zscheischler et al, 2014a, d, c) where water stress directly forces plants to close their stomata to limit transpiration, reducing photosynthesis. Similarly, Jung et al (2017) found that water availability is a much bigger control on the inter annual variability of GPP (IAV, which is controlled to a large degree by extreme events) compared to a smaller temperature control on a global In contrast to the small response of GPP to heat, however, R eco generally increased during most high temperature extreme events (Fig.…”
supporting
confidence: 91%
“…Teuling et al, 2010). Other important aspects to include in future studies are the timing of the extreme during the growing season, which can significantly influence the response (Schwalm et al, 2010;De Boeck and Verbeeck, 2011;Wolf et al, 2013). Eddy covariance measurements continue to be collected so for several FLUXNET sites increasingly long time series are becoming available.…”
mentioning
confidence: 99%
“…Due to the stochastic nature of the turbulent flow, there is always a random error component in the observations. In addition, imperfect spectral corrections and gap-filling procedures as well as calibration problems may be sources of systematic errors (Richardson et al, 2012;Wilson et al, 2002). The uncertainty of EC flux data is typically 20-30 % for annual carbon budget Baldocchi, 2003).…”
Section: Differences Between Observations and Site Simulationsmentioning
confidence: 99%
“…Granier et al (2008) reported that EWUE increased linearly with soil water deficit duration and intensity at a young beech forest site in north-eastern France. Moreover, EWUE also increased substantially at two forest sites, but not at grassland sites, during the 2011 spring drought in Switzerland (Wolf et al, 2013). However, no differences in EWUE were shown between abundant-and lowrainfall years at a boreal Scots pine forest site in southeastern Finland, even though GPP was reduced during lowrainfall years with long-lasting drought periods (Ge et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Mamolos et al [30] recorded an earlier maximum aboveground biomass of early-season species in response to drought in a Mediterranean lowland grassland. A case study in Switzerland indicates that the full flowering of dandelion and cocksfoot grass was 11 days earlier under spring drought than the annual mean flowering [31]. Using remote sensing datasets, the response of grassland phenology to drought on larger scales have been recently investigated.…”
Section: Introductionmentioning
confidence: 99%